Indication for primordial anisotropies in the neutrino background from the Wilkinson microwave anisotropy probe and the Sloan digital sky survey. - Trotta, R; Melchiorri, A (2005)
We demonstrate that combining cosmic microwave background anisotropy measurements from the 1st year Wilkinson Microwave Anisotropy Probe observations with clustering data from the Sloan galaxy redshift survey yields an indication for primordial anisotropies in the cosmological neutrino background.